Annually-resolved coral skeletal δ138/134Ba records: A new proxy for oceanic Ba cycling. (15th February 2019) - Liu, Yi; Li, Xiaohua; Zeng, Zhen; Yu, Hui-Min; Huang, Fang; Felis, Thomas; Shen, Chuan-Chou
Abstract: Barium/calcium ratios in the skeletons of scleractinian shallow-water corals have been used as proxies for coastal and oceanic processes such as river discharge, oceanic upwelling and surface ocean productivity. However, the variations in Ba/Ca ratios in aragonitic coral skeletons remain difficult to interpret as an environmental proxy. This difficulty is mainly due to the influence of internal (biomineralization) and multiple external (environmental) processes on Ba incorporation into coral skeletons, and these processes are hard to constrain with Ba/Ca alone. Here we present the first annually-resolved records of the Ba isotopic compositions (δ 138/134 Ba) in shallow-water corals ( Porites ) collected alive in the field, supplemented by the analysis of Ba/Ca ratios. Seven coral cores were recovered at different oceanic settings in the South China Sea, extending from the northern inner shelf to the central and southern deep basin. The annual δ 138/134 Ba records of six corals fell within a narrow range from 0.24 ± 0.03‰ to 0.38 ± 0. 03‰ (2SD), with a mean value of 0.33 ± 0.08‰ (2SD, N = 21). One single inner-shelf coral revealed low δ 138/134 Ba values (0.10 ∼ 0.11 ± 0.03‰), which might reflect the influence of terrestrial water/sediment. In contrast, the coral Ba/Ca ratios showed a wide range of intercolony differences, from 2 to 14 μmol/mol. This variation is too large to be ascribed to the changes in the Ba concentrations of seawater or other environmental parameters. Rayleigh fractionation between corals and seawater during biomineralization was proposed to explain the anomalous variations in the Ba/Ca ratios observed in coral skeletons. However, this result is incompatible with the relatively constant Ba isotopic compositions in coral. Instead, we suggest that the probable precipitation of witherite (BaCO3 ) within the domains of aragonite under oversaturated calcifying fluid could explain the large variability in the coral Ba/Ca ratios. The coral δ 138/134 Ba records from diverse oceanic settings were largely unaffected by biomineralization processes and temperature and displayed a relatively constant negative offset from typical surface seawaters. Our results suggest that Ba isotopes in Porites could be a proxy for reconstructing the δ 138/134 Ba of seawater and hence provide new insights into Ba cycling in the upper oceans in the past.